2011
DOI: 10.1017/s095457941100006x
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic flexibility and positive affect in parent–child coregulation and the development of child behavior problems

Abstract: Parent–child dyadic rigidity and negative affect contribute to children’s higher levels of externalizing problems. The present longitudinal study examined whether the opposite constructs of dyadic flexibility and positive affect predicted lower levels of externalizing behavior problems across the early childhood period. Mother–child (N = 163) and father–child (n = 94) dyads engaged in a challenging block design task at home when children were 3 years old. Dynamic systems methods were used to derive dyadic posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(201 citation statements)
references
References 69 publications
9
187
0
3
Order By: Relevance
“…Synchronous coregulation of emotion between parents and children, when paired with a high level of positive emotion, has been found to predict lower behavioral dysregulation in children (Lunkenheimer et al, 2011). Further, children's RSA seems to be related to behavioral synchrony in parent-child interaction; when there are fewer instances of behavioral and emotional synchrony, basal RSA tends to be lower in infants, indicating reduced physiological regulation (Feldman & Eidelman, 2007).…”
Section: Parent-child Coregulationmentioning
confidence: 96%
See 1 more Smart Citation
“…Synchronous coregulation of emotion between parents and children, when paired with a high level of positive emotion, has been found to predict lower behavioral dysregulation in children (Lunkenheimer et al, 2011). Further, children's RSA seems to be related to behavioral synchrony in parent-child interaction; when there are fewer instances of behavioral and emotional synchrony, basal RSA tends to be lower in infants, indicating reduced physiological regulation (Feldman & Eidelman, 2007).…”
Section: Parent-child Coregulationmentioning
confidence: 96%
“…When there is greater synchrony in parents' and children's emotional and behavioral expressions and physiological states (in other words, they tend to co-occur in real time), children's own self-regulatory abilities are promoted (Calkins, 2011;Feldman, 2012). For example, greater matching of positive affect between parents and preschool-aged children during parent-child interaction has been shown to contribute to the reduction of dysregulated behavior problems among children above and beyond children's positive affect alone (Lunkenheimer, Olson, Hollenstein, Sameroff, & Winter, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic systems approaches have offered a promising way to investigate coregulatory processes as this method captures the moment-to-moment processes inherent in dyadic interaction (DiDonato et al 2013;Lunkenheimer et al 2011). Historically, operationalizing emotional processes within dyadic contexts has been difficult but in the past decade, the systems perspective has provided an exciting means for studying dyads (Hollenstein 2011).…”
Section: Dynamic Systems Analysis Approach To Studying Emotion Coregumentioning
confidence: 99%
“…Results from their study indicated that parent-child affective rigidity was associated with chronic high levels of child internalizing problems, and rigidity predicted growth in child externalizing problems over time. Results from Lunkenheimer et al's (2011) longitudinal study of dyadic affective flexibility in young children and their parents added nuance to Hollenstein's initial findings. Specifically, the interaction between high levels of parent-child positive affect and high dyadic affective flexibility at time one predicted lower externalizing problems at time two.…”
Section: Is Flexibility Related To Youth Psychopathology?mentioning
confidence: 84%
“…In these cases just described, classification of dyads is more difficult. As such, researchers have tended to use the various metrics individually in analyses, though some recent studies have examined various metrics in tandem (e.g., Hollenstein and Lewis 2006) or attempted to model them as manifest indicators of a latent factor (e.g., Lunkenheimer et al 2011).…”
Section: Measurement and Operationalization Of Dyadic Affective Fleximentioning
confidence: 99%